Nina Schmidt. The Wounded Self: Writing Illness in Twenty-First-Century German Literature. Camden House, 2018. - Erika M Nelson Mukherjee (Studies in 20th & 21st Century Literature, 2019)
Review of Nina Schmidt. The Wounded Self: Writing Illness in Twenty-First-Century German Literature. Camden House, 2018. 235 pp.
Keywords: illness; German literature